Increasing the topological diversity of light with modulated Poincaré beams. (21st April 2021) - Darvehi, Pegah; Vicuña-Hernández, Verónica; Marrucci, Lorenzo; Piedipalumbo, Ester; Santamato, Enrico; Piccirillo, Bruno
Abstract: We introduce a wide class of singular inhomogeneously polarized beams characterized by a nonuniform rotation rate of the local polarization azimuth about a C- or a V-point. They are obtained by adding an extra phase modulation with an m -fold rotational symmetry to the helical wavefronts underpinning Poincaré beams. The resulting modulated Poincaré beams have been theoretically studied and experimentally generated using tailored space-varying-axis plates based on liquid crystals.